Early childhood mental health consultation: care providers' experiences of the consultative relationship - Kniegge, Krystal, author; Yuma, Paula, advisor; Miles, Brenda, committee member; Barrett, Karen, committee member (Colorado State University. Libraries, 2017)
This study examines child care teachers' experiences receiving early childhood mental health consultation (ECMHC). Although there is substantial research demonstrating that ECMHC is an effective intervention in helping teachers better address challenging behaviors in their classroom and promote a more nurturing classroom environment, there has not been any published research to date investigating teachers' personal experiences receiving consultation. Considering that teachers are the primary focus of most ECMHC interventions, the purpose of this study was to examine child care teachers' personal experiences receiving consultation. Eight child care teachers were interviewed for this study, and data from these interviews were used to construct a theoretical model for how child care teachers experience consultation. Results from this study indicated that most teachers found consultation to be helpful in addressing challenges and promoting protective factors in child care. The most meaningful components of the consultative relationship as identified by participants were consistency, confidence in the confidentiality of consultation, and teachers' perception of consultants' positive emotional responsiveness. The most significant benefits identified by participants were: 1) having space to speak freely, 2) brainstorming in consultation, 3) processing personal concerns in consultation, 4) feeling validated as a teacher, 5) gaining additional knowledge and skills, and 6) growing in self-awareness. Challenges experienced within the consultative relationship included unmet expectations of receiving immediate feedback from consultants, wanting consultants to spend more time working directly with children, and dealing with inconsistency in consultation. These results indicate the most helpful components of consultation, and speak to the challenges that arose in consultation, providing consultants and researchers with valuable insight into how ECMHC affects child care teachers. By examining the helpful and challenging dynamics of consultation identified by child care teachers, consultants and researchers can consider ways to expand and improve future implementation of ECMHC.
Keywords: child care; consultative relationship; teachers; consultation; challenging behaviors; early childhood mental health